2015
DOI: 10.1111/vco.12155
|View full text |Cite
|
Sign up to set email alerts
|

Canine small clear cell/T‐zone lymphoma: clinical presentation and outcome in a retrospective case series

Abstract: Published studies, taken together, suggest the existence of a single canine lymphoma entity, with a small clear cell appearance by cytological evaluation, a histopathological T-zone pattern and an aberrant CD45-negative T-cell phenotype, mostly characterized by long-term survival. We describe clinical presentation and outcome in a retrospective case series of canine small clear cell/T-zone lymphoma. Despite the reported predisposition of Golden retriever, this breed was not represented in our case series. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 18 publications
(46 reference statements)
6
69
2
Order By: Relevance
“…Cytologically, the neoplastic cells in similar in both canine and human TZL. In both species, they are small to medium-sized with a moderate amount of lightly stained cytoplasm and oval to elliptic nuclei with sharp, shallow indentations, finely granular chromatin, and inapparent nucleoli [67,69]. In both species, small numbers of large cells may be noted.…”
Section: T-cell Neoplasmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytologically, the neoplastic cells in similar in both canine and human TZL. In both species, they are small to medium-sized with a moderate amount of lightly stained cytoplasm and oval to elliptic nuclei with sharp, shallow indentations, finely granular chromatin, and inapparent nucleoli [67,69]. In both species, small numbers of large cells may be noted.…”
Section: T-cell Neoplasmsmentioning
confidence: 99%
“…In the dog, peripheral blood lymphocytosis is described in 48%–64% of cases and neoplastic cells can be detected in the peripheral blood in 100% of cases in which peripheral blood was available for flow cytometric analysis, including many cases in which the absolute lymphocyte count was normal [16,66,69]. Bone marrow involvement in both hTZL and cTZL appears uncommon and peripheral blood cytopenias are very uncommon [69,71]. Limited hTZL-specific immunophenotypic information is available, but the tumor cells are described as CD2+, CD3+, CD5+, and CD4+ [72].…”
Section: T-cell Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, dogs receiving no treatment for TZL lived a median of 22.6 months, while median survival for those receiving doxorubicin-based chemotherapy was 13.4 months, and for those receiving chemotherapy without doxorubicin it was 10.3 months (not statistically different) (Valli and others 2013). A more recent, smaller, study found that 26 dogs with TZL had long survival times (both with and without chemotherapy; median 24.9 months), but there was a subset of patients that had shorter survival times similar to HGTCL (Martini and others 2016). …”
Section: Treatmentmentioning
confidence: 99%
“…A further flow cytometry study identified TZL having lymphocytes that were CD4+, but had a specific aberrant lack of CD45 (ie, the cells are CD45 negative) (Seelig and others 2014). Lymphocytosis occurs in more than half of TZL patients (Flood-Knapik and others 2013, Martini and others 2016). …”
Section: Types Of Tcl In Dogsmentioning
confidence: 99%